2011
DOI: 10.3141/2248-02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Driver and Surrounding Traffic on Vehicle Deceleration Behavior at Onset of Yellow Indication

Abstract: This paper discusses driver deceleration levels in a controlled field environment at the onset of a yellow indication on high-speed signalized intersection approaches using an in-vehicle differential Global Positioning System. The impacts of driver gender, driver age, roadway grade, mean approach speed, platooning scenarios (leading, following, or alone), and time to intersection (TTI) on driver deceleration levels were analyzed. This information is critical for the efficient and safe design of traffic signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…At VTTI, Amer et al (11) and Li et al (12) conducted controlled field data collection efforts to model passenger car driver PRT and deceleration behavior at the onset of yellow indications as a function of various driver, vehicle, and traffic stream characteristics under different weather and roadway conditions. A comparison of driver PRT, deceleration levels, and driver stop-go behavior demonstrated that the results obtained from the controlled test environment were consistent with other empirical field observations and thus were valid for model development (14)(15)(16).…”
Section: Experimental Designsupporting
confidence: 79%
“…At VTTI, Amer et al (11) and Li et al (12) conducted controlled field data collection efforts to model passenger car driver PRT and deceleration behavior at the onset of yellow indications as a function of various driver, vehicle, and traffic stream characteristics under different weather and roadway conditions. A comparison of driver PRT, deceleration levels, and driver stop-go behavior demonstrated that the results obtained from the controlled test environment were consistent with other empirical field observations and thus were valid for model development (14)(15)(16).…”
Section: Experimental Designsupporting
confidence: 79%
“…The second test was executed at a single instructed speed of 72 km/h with no leading or following vehicles because the previous study did not find the lead or following vehicle to have a statistically significant impact on driver decisions to stop or go decisions, PRTs, and deceleration levels. A comparison of driver PRT, deceleration levels, and driver stop or go behavior demonstrated that the results obtained from the controlled test environment were consistent with other empirical field observations and thus are valid for model development (13)(14)(15)(16).…”
Section: Light-duty Vehicle Field Studysupporting
confidence: 79%
“…For example, in a controlled field test setting, El-Shawarby et al (2011) introduced other road users in the scene. Occasionally, a lead or a following vehicle appeared.…”
Section: Introductionmentioning
confidence: 99%